Validity and reliability analysis of the Servqual model adapted to supermarket retail - Santos, José Wendel dos; Alsina, Odelsia Leonor Sanchez de; Monteiro, Luciano Fernandes (Brazilian Journal of Production Engineering, 2020)
The instruments used to measure the quality of services provided by a given organization must have favorable properties of reliability and validity, to justify the confidence that is placed in the results they produce. In this sense, this study aimed to present the applicability of the statistical analysis to investigate the validity and reliability properties of the questionnaire provided to evaluate the quality of the services provided by a supermarket located in the city of Aracaju/SE. Based on the scores of 385 consumers, Multiple Linear Regression was applied to verify the validity of the questionnaire, while Cronbach's alpha to analyze the reliability of the questionnaire. In this analysis, it was observed that 78.8% of the variations in the degree of expectation and 80.3% of the variations in the degree of performance reported by consumers can be explained by the variation of the scores obtained in the evaluated dimensions. For the measurement of expectation, the alpha value was 0.87 and for the measurement of performance, it was 0.86. These values were considered satisfactory since the previous coefficients were above the thresholds recommended in the specialized literature. Thus, it is suggested that the questionnaire used to assess the quality of services in the supermarket was consistent and accurate
Keywords: Quality in services; supermarkets; validity; reliability